2016
DOI: 10.1088/1748-0221/11/03/c03043
|View full text |Cite
|
Sign up to set email alerts
|

The LICPA-driven collider—a novel efficient tool for the production of ultra-high pressures in condensed media

Abstract: A: Generation of strong shock waves for the production of Mbar or Gbar pressures is a topic of high relevance for contemporary research in various domains, including inertial confinement fusion, laboratory astrophysics, planetology and material science. The pressures in the multi-Mbar range can be produced by the shocks generated using chemical explosions, light-gas guns, Z-pinch machines or lasers. Higher pressures, in the sub-Gbar or Gbar range are attainable only with nuclear explosions or laser-based metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…That is why to determine this factor we used numerical simulations employing the two-dimensional (2D) hydrodynamic PALE code [26,27]. Based on the simulations performed for the parameters of the CH/Au target, the accelerator and the laser pulse such as those in the experiment (for more details see [28]) we found that for E L = 200 J the factor  ≈ 1.36 ± 0.02. These simulations also indicated that the moment the projectile is leaving the accelerator channel about 90 % of the mass and kinetic energy of the projectile is stored inside a small region of the size Δz p < 0.1 mm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why to determine this factor we used numerical simulations employing the two-dimensional (2D) hydrodynamic PALE code [26,27]. Based on the simulations performed for the parameters of the CH/Au target, the accelerator and the laser pulse such as those in the experiment (for more details see [28]) we found that for E L = 200 J the factor  ≈ 1.36 ± 0.02. These simulations also indicated that the moment the projectile is leaving the accelerator channel about 90 % of the mass and kinetic energy of the projectile is stored inside a small region of the size Δz p < 0.1 mm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that in the accelerator with a 200-J laser driver a 4-g gold plasma projectile can be accelerated to the velocity of 140 km/s with the energetic acceleration efficiency of 15 -19 % which is at least by a factor 5 -10 higher than those achieved in the ablative acceleration schemes and is the highest among the ones measured so far for any projectiles accelerated to the velocities ≥ 100 km/s. Such high acceleration efficiency coupled with the high density of the projectile driven by LICPA makes it possible to produce high-pressure shocks by the projectile impact much more efficiently than with the methods used so far [28]. As a result, to create high-energydensity matter states, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The simulations involve a heat conductivity numerical model [70] and heat flux limiter, simple critical-density and wave-based laser absorption models [71], Spitzer-Harm heat conductivity model [72] and realistic Quotidian equation of State [73]. This code is commonly used for interpretation of experiments involving nanosecond pulses [74][75][76]. The simulation uses a 2D computational r-z mesh containing 100 × 100 cells including a 40 nm thick and 25 µm long foil of solid aluminum at room temperature.…”
Section: Simulation Methods and Parametersmentioning
confidence: 99%